Strategy for Developing MSME’s Products through Halal Certification Labels in Batu Bara Regency - Hidayat Nasution, Muhammad Taufik; Syahriza, Rahmi; Fadhila Rahma, Tri Inda (Management of Zakat and Waqf Journal (MAZAWA), 2025)
This study analyzes the product development strategies of MSMEs in Batu Bara Regency through the improvement of halal certification status. MSMEs are a key component of the country's economic growth, especially in terms of increasing the competitiveness of local products and community welfare. Trust in MSME products tends to decline due to unguaranteed processes and quality. Emphasizing the importance of product legality and the application of sharia values in business activities, this study aims to examine the development strategies of MSMEs in Batu Bara Regency that have obtained halal certification. A descriptive qualitative methodology was used to obtain objective interview results. Interviews were conducted with MSME actors and authorities. The research findings show that the sustainability of halal MSMEs is influenced by external elements (opportunities and threats) and internal elements (strengths and weaknesses), which were identified through SWOT analysis. Based on the calculation findings, MSMEs are in quadrant II (Strengths–Threats) of the Cartesian SWOT diagram with an IFAS score of 3.11075 and an EFAS score of 3.31712. The ST strategy, which maximizes internal strengths to overcome various external challenges, including company competition and certification process barriers, is the best step in this case. Halal certification has been proven to strengthen the ability to build consumer trust, improve product quality, and open new markets, which helps MSMEs become more sustainable and competitive.